(untitled) (Global Journal of Science Frontier Research, 2017)
Land degradation is a major cause of Ethiopia’s low and declining agricultural productivity, continuing food insecurity, and abject rural poverty. The productivity of agricultural economy, which is the backbone of the country’s economy, is being seriously eroded by unsustainable land management practices both in areas of food crops and in grazing. Low land productivity due to land degradation in form of soil erosion is one of the leading challenges to improving the performance of the smallholder farming system sector in Ethiopia. In this context, the adoption of Sustainable Land Management practices/ technologies is quite crucial to increase agricultural productivity, ensure food security and improve the livelihoods of smallholder farmers. Farmers recommend various SLM practices/technologies for sustainable implementation, but adoption of such agricultural land management practices/ technologies is still very low. There is no clear understanding of the problems encountered by farmers in the adoption of recommended SLM practices/ technologies.